2008
DOI: 10.1037/a0012918
|View full text |Cite
|
Sign up to set email alerts
|

A predictive screening index for posttraumatic stress disorder and depression following traumatic injury.

Abstract: Posttraumatic stress disorder (PTSD) and major depressive episode (MDE) are frequent and disabling consequences of surviving severe injury. The majority of those who develop these problems are not identified or treated. The aim of this study was to develop and validate a screening instrument that identifies, during hospitalization, adults at high risk for developing PTSD and/or MDE. Hospitalized injury patients (n = 527) completed a pool of questions that represented 13 constructs of vulnerability. They were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
132
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(140 citation statements)
references
References 36 publications
1
132
0
5
Order By: Relevance
“…Indeed, factors occurring after the trauma, such as cognitive and emotional adaptation strategies, are involved in the development of PTSD and can modulate the effects of the peritraumatic events (Ehring et al, 2008;Jeavons, Horne, & Greenwood, 2000;O'Donnell et al, 2008;Donnell, Elliott, Wolfgang, & Creamer, 2007).…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, factors occurring after the trauma, such as cognitive and emotional adaptation strategies, are involved in the development of PTSD and can modulate the effects of the peritraumatic events (Ehring et al, 2008;Jeavons, Horne, & Greenwood, 2000;O'Donnell et al, 2008;Donnell, Elliott, Wolfgang, & Creamer, 2007).…”
Section: Discussionmentioning
confidence: 96%
“…Recently screening instruments have been developed that draw on a wider pool of items (e.g., O'Donnell et al, 2008;Winston, Kassam-Adams, Garcia-Espana, Ittenbach, & Cnaan, 2003). Symptom-based instruments have the advantage, however, that they may be applicable across a wider range of potentially traumatic events, and there is as yet no evidence that they are less effective at screening than more broadly based instruments.…”
Section: Discussionmentioning
confidence: 98%
“…91 Surrogate markers for a history of psychiatric problems (eg, seeking professional help for emotional problems) or traumatic events (eg, assault, sexual abuse, combat duty) have been shown to be significant risk factors for depression in both the TBI and general populations. 58,79 Less education 14,16,90 and lower IQ scores 92 have been implicated in higher depression rates after TBI, but 2 studies using DSM MD criteria found no effects for education. 6,19 In the general population, no differences in lifetime prevalence of MD was found among levels of education, but persons with 0-11 years' education had higher 12-month MD rates (OR 1.9, CI 1.3-2.8).…”
Section: Associated Psychosocial Educational and Occupational Featuresmentioning
confidence: 98%
“…25 Persons who reported irritability and anger soon after injury were at greater risk for developing post-TBI MD. 58 In the general population, impulse control disorders (16.6%, CI 13.0%-20.2%) were the second most common cooccurring disorder in persons with depression. 55 MD in the general population was a temporal antecedent of impulse control disorders in only 20.8% (CI 14.2%-27.3%) of cases.…”
Section: Associated Disordersmentioning
confidence: 99%